2021
DOI: 10.1021/acs.analchem.0c05219
|View full text |Cite
|
Sign up to set email alerts
|

Amplified Fluorescence by Hollow-Porous Plasmonic Assembly: A New Observation and Its Application in Multiwavelength Simultaneous Detection

Abstract: Surface plasmon coupled emission (SPCE) is a new analytical technique that provides increased and directional radiation based on the near-field interaction between fluorophores and surface plasmons but suffers from the limitation of insufficient sensitivity. The assembly of hollow-porous plasmonic nanoparticles could be the qualified candidate. After the introduction of gold nanocages (AuNCs), fluorescence signal enhancement was realized by factors over 150 and 600 compared with the normal SPCE and free space … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 47 publications
0
28
0
Order By: Relevance
“…Importantly, we also note the appearance of anisotropic shapes with pseudo-trapezoidal nanostructures. Therefore, these NPs display sharp nanotips, wherein the EM field enhancement is high due to intense electron density clouding. Additionally, the elemental analysis shown in Figure g confirms the presence of elemental Ag in the synthesized NPs along with silicon (Si), carbon (C), and oxygen (O). Since SWP is made up of C and O, we observe their characteristic peaks along with the Si peak contributed from the Si substrate used for SEM characterization.…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…Importantly, we also note the appearance of anisotropic shapes with pseudo-trapezoidal nanostructures. Therefore, these NPs display sharp nanotips, wherein the EM field enhancement is high due to intense electron density clouding. Additionally, the elemental analysis shown in Figure g confirms the presence of elemental Ag in the synthesized NPs along with silicon (Si), carbon (C), and oxygen (O). Since SWP is made up of C and O, we observe their characteristic peaks along with the Si peak contributed from the Si substrate used for SEM characterization.…”
Section: Resultsmentioning
confidence: 83%
“…The surface plasmons are collective excitation of these electron densities on a metalized (plasmonic) surface where the translational invariance is essentially broken perpendicular to the surface geometry . Consequently, plasmonic surfaces in nanoregimes while excited under the phase matching conditions sustain a coupled oscillation known as surface plasmon polaritons (SPPs) that propagate along the surface (in this case, polaritons are coupled oscillation of photons and plasmons). Recently, such SPPs supported by metallized thin films are progressively explored for fluorescence-based biosensor development in Kretschmann–Raether and reverse Kretchmann (RK) prism-coupled configurations on account of their ability to detect molecules at exceptionally trace concentrations. It has been observed that the fluorophores illuminated by a laser source on metallic nanofilms can in turn excite the SPPs which radiate toward the far field carrying the spectral information of the emission. Additionally, the fluorescence emission is greatly polarized on account of the core feature of SPPs to couple only with the transverse magnetic incident light.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, recently, gold nanocages and nanoshells have been reported in the SPCE platform to understand the effects from hollow plasmonic nanostructures toward dequenching the emission. The strong plasmonic coupling interactions between the hollow nanoparticles and the SPPs of metallic thin films provide a superior wavelength match, and an augmented EM field with a new radiation channel for significantly enhancing the sensitivity of biomolecules in the nanogap region. , These techniques were employed using quantum dots and gold nanoarchitectures to realize simultaneous enhancement in multiple wavelengths in the SPCE platform, amenable for multiplexed detection and imaging of different analytes . In this regard, we emphasize the utility of multiple hotspots supported by such anisotropic nanostructures toward dequenching the emission in SPCE.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The classic plasmon-based system, SPR, has been increasingly applied in sensing and clinical detection because of its sensitivity to refractive index variations, label-free detection, and real-time monitoring. , As the reverse process of SPR, surface plasmon-coupled emission (SPCE), whose amplified radiation is induced by a coupled interaction between the excited fluorophore nearby and the propagating surface plasmons around the metal substrate, is gradually developed with high detection sensitivity and excellent optical properties. Dealing with an increasingly complex actual system, higher requirements have been put forward for the detection method. Considering the intense EM field and the possible interactions between localized and propagating surface plasmons, the introduction of AuNPs in SPCE could create a new plasmon-based technology with enhanced emission and better detection performance.…”
Section: Introductionmentioning
confidence: 99%